Financing the development of the regional vocational training system: qualitative changes - Dvoryadkina Elena; Efimova Elena; Prostova Dina (SHS Web of Conferences, 2021)
Innovative development of the national economy is Russia's main strategic aim in a globally competitive environment. In general, innovation processes should start with transformations within regions, as it is the regions in Russia that form the basis of the national economic system. The purpose of this paper is to identify prospective directions for qualitative changes in the development of the regional vocational education system, which is the object of the study. The authors focus on the financing of regional vocational education system development, since this system is considered one of the most important factors of economic competitiveness, national security, and at the same time, vocational training is the basis for human capital accumulation and development. Regional programs, which are one of the instruments for financing education systems at regional level, are analyzed.